SARM Rad140 Increases Osteoblasts, Muscle Fiber Size, Myonuclei, and Reduces Osteoclasts in Orchidectomized Wistar Rats - Budaya, Taufiq Nur; Daryanto, Besut; Seputra, Kurnia Penta; Fabrianta, Dio Mafazi; Ekaputra, Aditya Airlangga; Dewi, RA Rose Khasana; Anita, Kenty Wantri; Dhani, Fauzan Kurniawan; Rofifa, Amira Fithri (Cell and BioPharmaceutical Institute, 2025)
Background: Orchidectomy is a surgical androgen deprivation therapy (ADT) for prostate cancer patients to achieve castrate testosterone levels. Selective androgen receptor modulators (SARMs) are used to mitigate the adverse effects of ADT, including elevated risk of osteoporosis, and reduced skeletal muscle mass. Rad140 is a novel SARMs that has high affinity for the androgen receptors. This study was conducted to determine the effects of SARM Rad140 on the number of osteoblasts, osteoclasts, muscle fiber cross-sectional area (CSA), muscle size, and number of myonuclei in rats underwent orchidectomy.Materials and Methods: An experimental study was conducted using a randomized post-test only control group design. Following orchidectomy, SARM Rad140 was administered orally for six weeks at various doses. Osteoblasts, osteoclasts, muscle fiber CSA, muscle size, and number of myonuclei were measured. Quantitative analysis was performed using one-way ANOVA.Results: There were significant differences in the effects of SARM Rad140 at different doses on osteoblast and osteoclast cells. At higher doses, the osteoblast cell counts in rats tended to increase, while the osteoclast counts tended to decline. The treatment group also showed significant results in the CSA of the gastrocnemius muscle fibers, as well as in the number of myonuclei of the gastrocnemius muscle.Conclusion: SARM Rad140 significantly increased the number of osteoblasts, muscle fiber CSA, and gastrocnemius muscle myonuclei, while decreasing osteoclasts. SARM Rad140 is a promising therapy for osteoporosis and muscle weakening due to ADT.Keywords: SARM Rad140, orchidectomy, osteoblasts, osteoclasts, muscle fiber cross sectional area, myonuclei